Cell type‐specific transcriptome analysis unveils secreted signaling molecule genes expressed in apical epithelial cap during appendage regeneration. (11th November 2019) - Okumura, Akinori; Hayashi, Tetsutaro; Ebisawa, Masashi; Yoshimura, Mika; Sasagawa, Yohei; Nikaido, Itoshi; Umesono, Yoshihiko; Mochii, Makoto
Abstract: Wound epidermis (WE) and the apical epithelial cap (AEC) are believed to trigger regeneration of amputated appendages such as limb and tail in amphibians by producing certain secreted signaling molecules. To date, however, only limited information about the molecular signatures of these epidermal structures is available. Here we used a transgenic Xenopus laevis line harboring the enhanced green fluorescent protein ( egfp ) gene under control of an es1 gene regulatory sequence to isolate WE/AEC cells by performing fluorescence‐activated cell sorting during the time course of tail regeneration (day 1, day 2, day 3 and day 4 after amputation). Time‐course transcriptome analysis of these isolated WE/AEC cells revealed that more than 8, 000 genes, including genes involved in signaling pathways such as those of reactive oxygen species, fibroblast growth factor (FGF), canonical and non‐canonical Wnt, transforming growth factor β (TGF β) and Notch, displayed dynamic changes of their expression during tail regeneration. Notably, this approach enabled us to newly identify seven secreted signaling molecule genes ( mdk, fstl, slit1, tgfβ1, bmp7.1, angptl2 and egfl6 ) that are highly expressed in tail AEC cells. Among these genes, five ( mdk, fstl, slit1, tgfβ1 and bmp7.1 ) were also highly expressed in limb AEC cells but the other two ( angptl2 and egfl6 ) are specifically expressed in tail AEC cells. Interestingly, there was no expression of fgf8 in tail WE/AEC cells, whose expression and pivotal role in limb AEC cells have been reported previously. Thus, we identified common and different properties between tail and limb AEC cells. Abstract : A cell type‐specific transcriptome analysis was performed using cells sorted from transgenic Xenopus tadpoles in which apical epithelial cap (AEC) cells were labeled with EGFP during tail regeneration. We identified several potential secreted signaling molecule genes expressed in AEC cells, and showed common and different properties between tail and limb AEC cells.